Effect of various phase fraction of bainite, intercritical ferrite, retained austenite and pearlite on the corrosion behavior of multiphase steels. (January 2021) - Neetu,; Katiyar, Prvan Kumar; Sangal, S.; Mondal, K.
Highlights: Effect of phase fraction/morphology on corrosion of multi-phase steels is studied. Multiphase interaction and rust constituents control the corrosion of the steels. Corrosion rate decreases with the introduction of pearlite in multiphase steels. The mechanism of corrosion changes as the various fraction of phases changes. Abstract: The work discusses the corrosion behavior of a set of newly developed high strength and highly ductile multiphase steels consisting of various fractions of bainite, intercritical ferrite, retained austenite and pearlite from the composition 0.67 % C, 1.71 % Si, 0.86 % Mn and 96.69 % Fe (wt.%). The steels were made by various combinations of continuous cooling in the ferrite-pearlite zone followed by austempering. Multiphase interaction and rust constituents uniquely control the corrosion of the steels. At a particular isothermal temperature, initial increase in corrosion rate with increment of continuous cooling time is followed by decrease in corrosion rate once pearlite starts appearing.